2019
DOI: 10.1002/mas.21616
|View full text |Cite
|
Sign up to set email alerts
|

Identification of MHC Peptides Using Mass Spectrometry for Neoantigen Discovery and Cancer Vaccine Development

Abstract: Immunotherapy with neoantigens presented by major histocompatibility complex (MHC) is one of the most promising approaches in cancer treatment. Using this approach, cancer vaccines can be designed to target tumor‐specific mutations that are not found in normal tissues. Clinical trials have demonstrated an increased immune response and eradication of tumors after injecting synthetic peptides selected from the immunopeptidome. Although the sequence of MHC binding peptides can be predicted from genome sequencing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 104 publications
(151 reference statements)
0
19
0
Order By: Relevance
“…Efforts have been made to further improve MS by, for example, prefixing it to high pressure liquid chromatography, to ensure higher purity of the samples, or by implementing tandem mass spectrometry, resulting in higher specificity [ 82 ]. Alone, MS does not suffice as a method for neo-antigen identification as it requires a priori knowledge of the potential target, although exceptions can be made for peptides spliced in the proteasome, peptides with post-translational modification (PTM) and peptides from non-coding regions [ 83 ]. However, because of its high sensitivity, accuracy and reproducible qualification and quantification of the HLA peptidome, it makes for a valid approach for neo-antigen validation.…”
Section: Identification and Validation Of Neo-antigensmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts have been made to further improve MS by, for example, prefixing it to high pressure liquid chromatography, to ensure higher purity of the samples, or by implementing tandem mass spectrometry, resulting in higher specificity [ 82 ]. Alone, MS does not suffice as a method for neo-antigen identification as it requires a priori knowledge of the potential target, although exceptions can be made for peptides spliced in the proteasome, peptides with post-translational modification (PTM) and peptides from non-coding regions [ 83 ]. However, because of its high sensitivity, accuracy and reproducible qualification and quantification of the HLA peptidome, it makes for a valid approach for neo-antigen validation.…”
Section: Identification and Validation Of Neo-antigensmentioning
confidence: 99%
“…IP is regarded as highly specific and flexible, allowing HLA-peptide isolation from a range of biological samples upon MAE. Although MAE without IP is a more time- and cost-effective approach, it lacks selectivity, as up to 60% of the eluted peptides can be contaminants [ 83 ]. Lanoix et al [ 90 ] compared both methods and concluded that both resulted in reproducible candidate neo-antigen libraries.…”
Section: Identification and Validation Of Neo-antigensmentioning
confidence: 99%
“…Neoantigen candidate selection relies on the spectra of somatic mutations identified by WES/RNA-seq. This approach suffers from a lack of direct experimental evidence of the real presence of predicted epitopes on the cell surface as a complex with MHC molecules [ 153 , 154 ]. Lacking data could be obtained using high-throughput mass spectrometry techniques [ 153 , 154 ] that at present allow us to analyze large amounts of peptides or whole proteins simultaneously.…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…This approach suffers from a lack of direct experimental evidence of the real presence of predicted epitopes on the cell surface as a complex with MHC molecules [ 153 , 154 ]. Lacking data could be obtained using high-throughput mass spectrometry techniques [ 153 , 154 ] that at present allow us to analyze large amounts of peptides or whole proteins simultaneously. This review does not aim to give a detailed characterization of MS-based approaches; for a comprehensive review on this topic, the reader could refer to [ 56 , 153 , 154 ].…”
Section: Mass Spectrometry-based Approachesmentioning
confidence: 99%
“…Genomics is not the only area that has undergone remarkable transformation recently in terms of the technologies and platforms that can be used to design, create, and study vaccines. Examples include the following: mass cytometry, which allows for incredibly complex immunophenotyping (24,25); proteomics and mass spectrometry (26)(27)(28)(29)(30); and metabolomics, which has been closely linked to immunologic function and vaccine response (31)(32)(33). However, in this focused review, we will explore how genomics and recent genomic technologies have impacted vaccine development and may provide solutions to both the long-standing barriers in vaccine design and the new challenges posed by new and re-emerging pathogens of public health importance.…”
Section: Introductionmentioning
confidence: 99%